Pengaruh Pengetahuan Akuntansi, Skala Usaha, Pengalaman Usaha, Dan Jenis Usaha Terhadap Penggunaan Informasi Akuntansi Pada Usaha Kecil Menengah Di Kota Tarakan - Sudarto, Sudarto (Ekonomika, 2010)
The purpose of this reseacher is to determine the effect of accounting knowledge, scale of business, business experience and the types of businesses to use accounting information to small and medium industries. Results of research by multiple liniear regression showed a regression coefficient of know ledge (X1), scale (X2), business experience (X3), business type (X4) marked positive except the type of business marked with a negative. This results meaning that independent variables influence the the direction of the variable dependent.Â If the value of the indpendent variable incrases or decreases will be encouraged to raise or lower the use of accounting information. Then there are positive and significant influence of knowledge of accounting, business scale, business experience and the type of business against the use of accounting information on Small and Medium Industries in the CIty of Tarakan.Â Key Words: Knowledge Accounting, Business Scale, Experience Of Business, Business Type, Use Of Accounting Information